2018
DOI: 10.1111/jace.16197
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of C3S in presence of CA: Mineral‐pore solution interaction

Abstract: C3S and CA are the main phases of OPC and Fe‐rich CAC, respectively. The objective of this research was to investigate the influence of CA on C3S hydration, representing an under sulfated OPC‐rich binder, and to shed light on the underlying hydration mechanisms. To this end, C3S was blended with 1‐30 wt‐% CA and the pastes (w/c 0.5) were investigated by heat flow calorimetry, in situ X‐ray diffraction and analysis of the pore solution chemistry. CA additions ≥5 wt‐% reveal a separation into three distinct heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Such calcium aluminate-based systems are commonly used as accelerators for various applications such as selflevelling mortar and tile adhesive. There are some studies in literature which talk about the hydration mechanisms of such systems [14][15][16], however, those studies do not focus in the first hour of acceleration. Nehring et al reported that ettringite is the major hydration product that forms in the first few hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such calcium aluminate-based systems are commonly used as accelerators for various applications such as selflevelling mortar and tile adhesive. There are some studies in literature which talk about the hydration mechanisms of such systems [14][15][16], however, those studies do not focus in the first hour of acceleration. Nehring et al reported that ettringite is the major hydration product that forms in the first few hours.…”
Section: Introductionmentioning
confidence: 99%
“…In another study by Nehring et al, where they studied the hydration of C 3 S in presence of CA, it was concluded that C 3 S can dissolve even at high Al concentrations in the pore solution. The reason mentioned was that the additional Ca ions needed for precipitation of calcium aluminate hydrates comes from C 3 S [16].…”
Section: Introductionmentioning
confidence: 99%